1991
DOI: 10.1016/1010-7940(91)90211-2
|View full text |Cite
|
Sign up to set email alerts
|

Survival and prognosis following resection of primary non small cell bronchogenic carcinoma

Abstract: A prospective follow up was carried out on 479 consecutive patients who underwent lung resection for non small cell primary bronchogenic carcinoma between 1980 and 1987 under the care of one surgeon at Guy's Hospital and Brook Hospital, London. The mean age of patients was 61.8 years; 16.9% were aged 70 years or over. Of the 479,237 patients had stage I disease, 108 patients stage II disease, and 134 patients stage III. Lobectomy was performed in 280 patients, pneumonectomy in 191, and wedge resection in 8. Op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
23
1
3

Year Published

1995
1995
2009
2009

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(31 citation statements)
references
References 17 publications
4
23
1
3
Order By: Relevance
“…This mortality is 2.5-fold to 4-fold lower than the 26% mortality reported from the Intergroup trial and consistent or slightly higher than other reports of pneumonectomy alone or chemotherapy followed by pneumonectomy (Table 4). 2,3,17,18 The results from this study of a 6% 30-day mortality rate are comparable to our own published data showing a 30-day mortality rate of 4% after pneumonectomy without induction therapy. 19 In addition, only 4 patients in the current series developed fatal pulmonary complications compared with the 11 patients who died as a result of ARDS (21%) in the Intergroup study.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This mortality is 2.5-fold to 4-fold lower than the 26% mortality reported from the Intergroup trial and consistent or slightly higher than other reports of pneumonectomy alone or chemotherapy followed by pneumonectomy (Table 4). 2,3,17,18 The results from this study of a 6% 30-day mortality rate are comparable to our own published data showing a 30-day mortality rate of 4% after pneumonectomy without induction therapy. 19 In addition, only 4 patients in the current series developed fatal pulmonary complications compared with the 11 patients who died as a result of ARDS (21%) in the Intergroup study.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, the overall treatment-related mortality was acceptable at 10%, with pneumonectomy patients having a higher mortality rate (15%), which is consistent with the known increased mortality observed in patients undergoing pneumonectomy compared with lesser resections. 2,3 The results of this trial prompted a North American Intergroup trial evaluating chemoradiation followed by surgery versus chemoradiotherapy alone for patients with stage III NSCLC. This latter trial demonstrated a statically significant reduction in local failure (22% vs 10%; P 5 .002) and improvement in progression-free survival (PFS) (22.4% vs 11.1%; P 5 .017) in patients receiving the trimodality approach without a difference in overall survival.…”
mentioning
confidence: 99%
“…Some recommend different limits for different resections [18]. In spite of this consensus for identifying patients at risk, about 30% develop cardiopulmonary complications with a 30 day mortality of 0.6-5% [18][19][20], depending on the surgical procedure.Both the respiratory and cardiovascular systems are under stress during physical exercise because of the oxygen requirement of working muscles, and carbon dioxide is produced. An increase in this gas exchange implies a close coupling of pulmonary ventilation and cardiovascular circulation.…”
mentioning
confidence: 99%
“…Some recommend different limits for different resections [18]. In spite of this consensus for identifying patients at risk, about 30% develop cardiopulmonary complications with a 30 day mortality of 0.6-5% [18][19][20], depending on the surgical procedure.…”
mentioning
confidence: 99%
“…No G:C to A:T glycine to aspartic acid transitions were observed in codon 13 using the ARMS technique. All of the mutations were found to be at the second resection (11,12). Thus rapid, early and accurate identification of mutations in the K-ras gene would aid in the diagnosis of lung cancer at a potentially curable stage of the disease.…”
Section: Resultsmentioning
confidence: 97%